International Conference on Wireless, Intelligent, and Distributed Environment for Communication WIDECOM 2018 (Cham : Springer International Publishing, 2018)
This book presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2018), organized by SRM University, NCR Campus, New Delhi, India, February 16-18, 2018. The conference focuses on challenges with respect to the dependability of integrated applications and intelligence-driven security threats against the platforms supporting these applications. The WIDECOM 2018 proceedings features papers addressing issues related to the new dependability paradigms, design, control, and management of next generation networks, performance of dependable network computing and mobile systems, protocols that deal with network computing, mobile/ubiquitous systems, cloud systems, and Internet of Things (IoT) systems. The proceeding is a valuable reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners, in industry, in the aforementioned areas. The book's structure and content is organized in such a manner that makes it useful at a variety of learning levels. Presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2018), organized by SRM University, NCR Campus, New Delhi, India, February 16-18, 2018; Includes an array of topics related to new dependability paradigms, design, control, and management of next generation networks, performance of dependable network computing and mobile systems, protocols that deal with network computing, mobile/ubiquitous systems, cloud systems, and Internet of Things (IoT) systems; Addresses issues related to the design and performance of dependable network computing and systems and to the security of these systems. .
Chapter1: Tamper Detection Using Fragile Image Watermarking Based on Chaotic System -- Chapter2: Cryptanalysis and Improvement of a User Authentication Scheme for SIP -- Chapter3: SECURITY AGAINST VAMPIRE ATTACK IN ADHOC WIRELESS SENSOR NETWORK: DETECTION & PREVENTION TECHNIQUES -- Chapter4: Securing Fuzzy Commitment Scheme against Decodability Attack based Cross-matching -- Chapter5: PiFallD: A Portable Fall Detection System -- Chapter6: Analysing, Designing, Implementation and Coding E-commerce through UX -- Chapter7: Performance evaluation of GAER over various crossover techniques in opportunistic networks -- Chapter8: Software Performance Measuring Benchmarks.-Chapter9: Texture Analysis of Fruits for its Deteriorated Classification -- Chapter10: Analysis of Packet Size Variation Supporting QoS for Survivable Optical High Speed Networks -- Chapter11: AN IMPROVED HYPRID ALGORITHM FOR WEB USAGE MINING -- Chapter12: Optimal Cache Placement by Identifying Possible Congestion Points in Wireless Sensor Networks -- Chapter13: Automatic Detection of Eczema Using Image Processing -- Chapter14: RECOGNITION OF EMOTIONS OF SPEECH AND MOOD OF MUSIC: A REVIEW -- Chapter15: Estimation of Probability Density Function of Digital Substrate Noise in Mixed Signal System -- Chapter16: Location Aware Data Distribution in P2P Mobile Cloud -- Chapter17: EPR: An Encounter and Probability based Routing Protocol for Opportunistic Networks -- Chapter18: Performance Comparison Simulation Model of Ad Hoc Cloud Network with Cloud Servers -- Chapter19: Path Restoration Versus Link Restoration in Survivable ATM Networks -- Chapter20: Adaptive Error Control Technique for Cluster based Underwater Wireless Sensor Networks -- Chapter21: Analysis of Basic Cognitive Radio and Queuing Based Request Handling -- Chapter22: Time Validity Based Message Transmission for College Activities.
Engineering
text file PDF
Keywords: Electrical engineering; Microwaves; Optical engineering; Computer communication systems; Computers